Biomolecular sensing by surface-enhanced Raman scattering of monolayer Janus transition metal dichalcogenide. Issue 19 (9th May 2020) - Jia, Shuai; Bandyopadhyay, Arkamita; Kumar, Hemant; Zhang, Jing; Wang, Weipeng; Zhai, Tianshu; Shenoy, Vivek B.; Lou, Jun
Abstract : In this work, we demonstrate that monolayer Janus MoSSe is an effective and universal platform for enhancing Raman signal and detecting biomolecules for the first time. Abstract : In this work, we demonstrate that monolayer Janus MoSSe is an effective and universal platform for enhancing Raman signal and detecting biomolecules for the first time. The out-of-plane dipoles in monolayer Janus MoSSe redistribute charges of adsorbed biomolecules, polarize biomolecules and enhance their Raman vibrational intensity. The estimated Raman enhancement factor is higher than 10 5, which is comparable with the highest reported enhancement factor for 2D substrates. The C–C stretching Raman peak around 1360 cm −1 is used to indicate the glucose concentration, and its peak-integrated intensity increases linearly with the glucose concentration in the range of 1–10 mM. DFT calculations also confirm that charge redistribution in glucose induced by dipole interactions can enhance Raman intensity significantly when glucose molecules are adsorbed onto monolayer Janus MoSSe.